2009
DOI: 10.1002/pmic.200800598
|View full text |Cite
|
Sign up to set email alerts
|

Biospecific irreversible fishing coupled with atomic force microscopy for detection of extremely low‐abundant proteins

Abstract: In the absence of an analog of PCR for proteins, the concentration detection limit (DL) becomes a real challenge. The problem may be solved by means of a combination of biospecific irreversible fishing with atomic force microscopy (AFM). AFM offers the ability to register individual molecules and their complexes, while biospecific fishing takes advantage of an affine interaction between analyte molecules spread over a large volume of biomaterial and ligand molecules immobilized on the chip surface. Fishing may… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
75
0
20

Year Published

2011
2011
2017
2017

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 78 publications
(95 citation statements)
references
References 51 publications
0
75
0
20
Order By: Relevance
“…1 Detection of protein immune complexes in pure solutions has been the subject of a large number of studies, which have shown that the difference between the immune complexes and immobilized antibodies can be determined from the difference in the heights of the objects detected by AFM. 1,[5][6][7][8][9][10] This approach was used to identify viral particles in solutions and biological fluids, eg, sputum and urine. 11 Since the size of viral particles exceeds that of proteins, viral particles can be detected more easily as compared with pure proteins.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1 Detection of protein immune complexes in pure solutions has been the subject of a large number of studies, which have shown that the difference between the immune complexes and immobilized antibodies can be determined from the difference in the heights of the objects detected by AFM. 1,[5][6][7][8][9][10] This approach was used to identify viral particles in solutions and biological fluids, eg, sputum and urine. 11 Since the size of viral particles exceeds that of proteins, viral particles can be detected more easily as compared with pure proteins.…”
Section: Introductionmentioning
confidence: 99%
“…Atomic force microscopy (AFM) is commonly used to visualize proteins and their complexes in near-native conditions. [1][2][3][4] The advantage of an AFM-based molecular detector lies in its ability to detect protein macromolecules and their complexes in single-molecule counting mode. 1 Detection of protein immune complexes in pure solutions has been the subject of a large number of studies, which have shown that the difference between the immune complexes and immobilized antibodies can be determined from the difference in the heights of the objects detected by AFM.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8,9,39,40 Images of the chip surface with immobilized antibodies and without antibodies after incubation in 10 -8 M gp120 solution are presented in Figure 4B and C. The objects with heights from 1.2 nm to 4 nm were visualized on the AFM chip surface with immobilized antibodies after incubation ( Figure 4B). The respective densities of object distribution with heights ρ(h) are on the Figure 4C.…”
mentioning
confidence: 99%
“…4 Analyzers in the recording part of these devices can be optical, 5 electrical, 6,7 or even nanomechanical, such as atomic force microscopy (AFM). 8 To perform a biospecific direct detection of proteins in this case, it is necessary to use molecular probes (antibodies or aptamers) covalently immobilized on the chip surface. Implementation of these chips for detection of proteins in the analyte is restrained by a limited variety of commonly used molecular probes such as antibodies.…”
mentioning
confidence: 99%